Thermodynamic Parameters of Lead Sulfide Crystals in the Cubic Phase - Volochanska, B. P. (Physics and Chemistry of Solid State, 2015)
Geometric and thermodynamic parameters of cubic PbS crystals were obtained using the computer calculations of the thermodynamic parameters within density functional theory method DFT. Cluster models for the calculation were based on the analysis of the crystal and electronic structure. Temperature dependence of energy ΔE and ΔH enthalpy, Gibbs free energy ΔG, heat capacity at constant pressure CP and volume CV, entropy ΔS were determined on the basis of ab initio calculations of the crystal structure of molecular clusters. Analytical expressions of temperature dependences of thermodynamic parameters which were approximated with quantum-chemical calculation points using mathematical package Maple 14 were presented. Experimental results compared with theoretically calculated data.